The "P" Word: Trans Men, Stone Butches and the Politics of Penetration - Noble, Bobby (Atlantis)

(untitled) (Mount Saint Vincent University, 2007)
The practice of sexual penetration has long been a site of contestation in butch-femme, queer and, more recently, female to male transsexual public cultures. Tracking representations of penetration in several documentaries about female and transsexual masculinities, this paper suggests that not only does penetration mark ambivalent spaces of sexual and gender incoherence, it also signals a resistance to the heteronormative potencies of shame.